Analysis of Information and Communication Technology Influence on Poverty Levels Using Analytical Hierarchy Process - Megie, Putri x; Kiswanto, Kiswanto (Komunitas Dosen Indonesia, 2026)
The role of Information and Communication Technology (ICT) in driving economic growth and reducing poverty has attracted increasing global attention. Yet, limited research has systematically prioritised ICT indicators that influence poverty at the regency level in developing countries. In this study, poverty is operationalised as a multidimensional socioeconomic condition reflected through regional deprivation indicators reported by official statistics, serving as the dependent construct influenced by ICT development factors. This study aims to analyse the influence of ICT on poverty levels in Bangka Regency by determining the priority weights for four ICT indicators—network infrastructure, community ICT access, digital literacy, and ICT utilisation in economic sectors—using the Analytical Hierarchy Process (AHP). A quantitative approach was employed, collecting pairwise comparison data from 100 respondents comprising local government officials, academics, and practitioners. The AHP analysis, validated with a Consistency Ratio (CR) of 0.05, revealed that network infrastructure received the highest priority weight (0.36), followed by ICT utilisation in economic sectors (0.29), community ICT access (0.20), and digital literacy (0.15). Methodologically, this study advances existing ICT–poverty research by providing a structured multi-criteria prioritisation framework that complements conventional econometric approaches through expert-based weighting of interrelated ICT dimensions. However, the findings are subject to limitations related to reliance on expert judgment and the absence of direct empirical modelling of poverty outcomes. These results highlight that infrastructure and productive ICT use are the most influential drivers, offering actionable guidance for evidence-based policy design and resource allocation in local governance contexts for sustainable poverty alleviation.